Teachers’ Perceptions of the Implementation of Teacher Certification in State Junior High Schools in Gabus District Grobogan Regency - Salafudin; Wasino (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2026)
This study aims to describe and analyze teachers’ perceptions of the implementation of teacher certification in State Junior High Schools in Gabus District, Grobogan Regency, reviewed from the understanding of the purpose of certification, the perceived benefits, and its implications for teacher professionalism and performance. This study uses a descriptive quantitative approach with a survey method. The research sample consisted of 92 certified teachers who were determined through a total sampling technique. Data were collected using a closed-ended questionnaire based on the Likert scale and analyzed with descriptive statistics. The results of the study showed that teachers’ perceptions of the implementation of certification were in the very good category, shown by a high average score, relatively homogeneous data distribution, and the tendency of answers centered on the category of very agree. These findings indicate that teacher certification is perceived to be effective in improving teacher competence, motivation, professionalism, and performance. Thus, teacher certification has a strategic role in supporting teacher professional development and improving the quality of learning in the context of regional education. Keywords: Teacher Perception, Teacher`s Certification, Teacher Performance. Abstrak: Guru merupakan aktor kunci dalam peningkatan mutu pendidikan, sehingga penguatan profesionalisme guru menjadi agenda strategis dalam kebijakan pendidikan nasional. Salah satu instrumen kebijakan yang dikembangkan pemerintah adalah program sertifikasi guru. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis persepsi guru terhadap pelaksanaan sertifikasi guru di SMP Negeri se-Kecamatan Gabus Kabupaten Grobogan, ditinjau dari pemahaman tujuan sertifikasi, manfaat yang dirasakan, serta implikasinya terhadap profesionalisme dan kinerja guru. Penelitian ini menggunakan pendekatan kuantitatif deskriptif dengan metode survei. Sampel penelitian terdiri dari 92 guru bersertifikat yang ditentukan melalui teknik total sampling. Data dikumpulkan menggunakan kuesioner tertutup berbasis skala Likert dan dianalisis dengan statistik deskriptif. Hasil penelitian menunjukkan bahwa persepsi guru terhadap pelaksanaan sertifikasi berada pada kategori sangat baik, ditunjukkan oleh nilai rata-rata yang tinggi, penyebaran data yang relatif homogen, serta kecenderungan jawaban yang terpusat pada kategori sangat setuju. Temuan ini mengindikasikan bahwa sertifikasi guru dipersepsikan efektif dalam meningkatkan kompetensi, motivasi, profesionalisme, dan kinerja guru. Dengan demikian, sertifikasi guru memiliki peran strategis dalam mendukung pengembangan profesional guru dan peningkatan kualitas pembelajaran pada konteks pendidikan daerah. Kata kunci: sertifikasi guru, persepsi guru, profesionalisme guru, kinerja guru.